2023
DOI: 10.1126/science.abn9057
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular organic matter in samples of the asteroid (162173) Ryugu

Abstract: Samples of the carbonaceous asteroid (162173) Ryugu were collected and brought to Earth by the Hayabusa2 spacecraft. We investigated the macromolecular organic matter in Ryugu samples and found that it contains aromatic and aliphatic carbon, ketone, and carboxyl functional groups. The spectroscopic features of the organic matter are consistent with those in chemically primitive carbonaceous chondrite meteorites that experienced parent-body aqueous alteration (reactions with liquid water). The morphology of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 80 publications
7
53
0
Order By: Relevance
“…These points, hereafter referred to as D-rich outliers, were also occasionally observed in previous measurements of unmetamorphosed carbonaceous chondrites (Piani et al , 2021. The relatively moderate C/H ratios of these D-rich outliers (Figures 2(A); A4) and the limited D-enrichments found for the IOM isolated from Ryugu's rocks compared to CI or CM chondrites (δD ∼ +400‰ obtained from bulk mass spectrometry in Yabuta et al 2023; δD ∼ +530‰ obtained by NanoSIMS in Ito et al 2022) preclude them from simply being interpreted as IOM-rich areas. The D-rich outliers could rather correspond to areas including one or several submicron-sized D-rich organic hot spots as observed by ion imaging both in Ryugu's bulk particles (either IOM or soluble organics) and in IOM (δD up to +8000‰; Yabuta et al 2023) and more generally in pristine carbonaceous chondrites (e.g., Remusat et al 2010).…”
Section: Nature Of the D-rich Outlierssupporting
confidence: 74%
See 4 more Smart Citations
“…These points, hereafter referred to as D-rich outliers, were also occasionally observed in previous measurements of unmetamorphosed carbonaceous chondrites (Piani et al , 2021. The relatively moderate C/H ratios of these D-rich outliers (Figures 2(A); A4) and the limited D-enrichments found for the IOM isolated from Ryugu's rocks compared to CI or CM chondrites (δD ∼ +400‰ obtained from bulk mass spectrometry in Yabuta et al 2023; δD ∼ +530‰ obtained by NanoSIMS in Ito et al 2022) preclude them from simply being interpreted as IOM-rich areas. The D-rich outliers could rather correspond to areas including one or several submicron-sized D-rich organic hot spots as observed by ion imaging both in Ryugu's bulk particles (either IOM or soluble organics) and in IOM (δD up to +8000‰; Yabuta et al 2023) and more generally in pristine carbonaceous chondrites (e.g., Remusat et al 2010).…”
Section: Nature Of the D-rich Outlierssupporting
confidence: 74%
“…The first reports for Ryugu indicated that its bulk hydrogen isotopic composition δD = 252‰ ± 13‰, expressed in δ notation (‰) relative to the standard mean ocean water ratio D/H SMOW = 155.76 × 10 −6 (Naraoka et al 2023), is higher than most of the values measured so far for bulk CI chondrites: Orgueil δD = +182‰ ± 44‰, Ivuna δD = +232 ± 60‰ and Alais δD = +89‰ ± 63‰ (±2 standard deviations; data compilation in Piani et al 2021). In contrast, the D/H of the insoluble organic matter (IOM) obtained after mineral removal by acid dissolution appears be lower in Ryugu (δD = +306‰ and +440‰ for sites A and C, respectively; Yabuta et al 2023) than in the IOM of CI chondrites (δD ≈ +1000‰; Alexander et al 2007).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations